2005
DOI: 10.1111/j.1439-0523.2005.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake and remobilization in tetraploid 'Langdon' durum wheat and a recombinant substitution line with the high grain protein gene Gpc-B1

Abstract: Tetraploid wheat (Triticum turgidum L. var. durum) cv. ‘Langdon’ (LDN) and its near‐isogenic recombinant substitution line no. 68 (RSL no. 68) carrying the high grain protein gene Gpc‐B1 from emmer wheat, were compared in three greenhouse experiments to establish in which way Gpc‐B1 increases grain protein concentration (GPC). At anthesis, RSL no. 68 had higher soluble protein and amino acids concentrations in the flag leaf than LDN. At maturity, both lines presented a similar above ground biomass and grain yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 27 publications
7
56
1
6
Order By: Relevance
“…RubisCO). This hypothesis is supported by previous studies in tetraploid wheat, which showed that lines with the non-functional GPC-B1 allele had significantly lower concentrations of soluble amino acids in the flag leaf than their corresponding isogenic lines carrying the functional GPC-B1 allele (Kade et al 2005). The concentration of soluble amino acids is important because a substantial percentage of the N in the wheat grain is supplied by amino acids remobilized from vegetative tissues (Barneix 2007;Gregersen et al 2008;Waters et al 2009).…”
Section: N Accumulation During Grain Developmentsupporting
confidence: 73%
See 1 more Smart Citation
“…RubisCO). This hypothesis is supported by previous studies in tetraploid wheat, which showed that lines with the non-functional GPC-B1 allele had significantly lower concentrations of soluble amino acids in the flag leaf than their corresponding isogenic lines carrying the functional GPC-B1 allele (Kade et al 2005). The concentration of soluble amino acids is important because a substantial percentage of the N in the wheat grain is supplied by amino acids remobilized from vegetative tissues (Barneix 2007;Gregersen et al 2008;Waters et al 2009).…”
Section: N Accumulation During Grain Developmentsupporting
confidence: 73%
“…Increasing the rate of N remobilization to developing grains utilizes stored N more efficiently and increases GPC (Kade et al 2005). While most of the carbohydrates found in the wheat grain are the result of assimilation during the grain filling period (Austin et al 1977a;Blake et al 2007), grain protein is predominantly derived from the remobilization of N from degraded leaf proteins, which are stored during wheat vegetative growth (Dalling et al 1976;Austin et al 1977b;Simpson et al 1983;Kichey et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Uauy et al (2006a) discovered that the Gpc-B1 DIC allele accelerates leaf senescence and suggested that the differences in GPC were pleiotropic effects of the changes in senescence. The effect of Gpc-B1 on senescence also explains the higher levels of soluble proteins and amino acids observed in flag leaves after anthesis in plants carrying the DIC Gpc-B1 allele relative to those with the LDN allele (Kade et al 2005). Chromosome 6B from DIC has been previously associated with higher grain mineral concentrations (Cakmak et al 2004), an effect that was later determined to be associated with the 250 kb region including Gpc-B1 (Distelfeld et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Even so, higher rates of N remobilization were associated with the higher grain protein concentration of nearly isogenic recombinant substitution lines carrying the high grain protein concentration Gpc-B1 locus from wild emmer wheat (Triticum turgidum subsp. dicoccoides; Kade et al, 2005;Uauy et al, 2006). All of these results indicate that efforts to increase N availability during grain filling should focus on processes related to N assimilation and temporary storage in vegetative organs rather than on protein degradation and translocation.…”
mentioning
confidence: 98%